The Effect of Application of The Benson Relaxation Technique on Reducing The Scale of Pain in Patients Post-Odontectomy Operation - Aprilina, Reza Asri; Supriyanto, Irwan; Heriyanto, Yonan (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
Pain can be controlled through pain management which aims to reduce pain to a comfort level. The Benson relaxation technique is a relaxation method that combines breathing with words that contain elements of belief that can help achieve a higher level of health and well-being. This study aims to determine the effect of the Benson relaxation technique on reducing the pain scale in patients after odontectomy surgery. This type of research is a pre-experimental design with a one-group pretest post-test design. Population: all 125 patients after odontectomy surgery. Patient selection was carried out using a purposive sampling technique of 56 patients. Data analysis used univariate and bivariate with the Mann-Whitney Test. The results of the study obtained a p-value of 0.000, which means that there was an influence before and after being given the Benson relaxation technique on reducing the pain scale after odontectomy surgery. Thus, it can be concluded that the Benson relaxation technique affect reducing the pain scale in patients after odontectomy surgery at RSKGM Bandung City.